Variabilidade entre materiais genéticos de eucalyptus spp quanto à distribuição de raízes finas em latossolos profundos - Pinheiro, Rafael Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Root behavior in deep soil layers is a subject poorly known for tree species. This topic can be important for breeding programs because a fast displacement of the root front is likely to explain different survival rates among clones in deep Ferralsols during exceptional drought periods. Although an inter-clonal variability in root development might account for different strategies to take up large amounts of water stored in deep soil layers after clearcutting, fine root distributions below a depth of 1 m have been poorly investigated for eucalypt clones. The objectives of our study were: a) to assess the inter-clonal variability among different Eucalyptus genetic materials in fine root densities down to the root front in 2 and 4-years-old clonal tests and in soils with different textures; b) to assess if the ratio between leaf area index (LAI) and root area index (RAI) was similar for different Eucalyptus genetic materials; and c) to assess if the relationship between mean stand height and maximum fine roots depth, as already found for a single E. grandis progeny, is similar for all genetic materials. Soils were sampled using a cylindrical auger at several distances from trees, down to a depth of 17 m for each genetic material. Fine roots (≤ 2 mm in diameter) and leaves were scanned and analysed by WinRhizo and ImageJ softwares, respectively. Fine root densities dropped from 0.2-0.4 g kg-1 in the upper soil layer to values < 0.1 g kg-1 below a depth of 25 cm, irrespective of the genetic material. Seedlings and clones exhibited a similar pattern of fine root development in very deep soil layers. However, mean fine root densities were higher for the seedlings and one clone (clone 14) than for the 2 other clones. Soil water content profiles showed that all the clones and seedlings had the capacity to withdraw water down to ...

O comportamento de raízes em camadas profundas do solo é um assunto pouco estudado entre espécies arbóreas. Este tema pode ser importante para programas de melhoramento genético, pois um crescimento rápido das raízes em profundidade pode contribuir para explicar diferentes taxas de sobrevivência entre clones nos Latossolos profundos, em períodos excepcionalmente secos. Os objetivos do estudo foram: a) avaliar a densidade de raízes finas de diferentes materiais genéticos de Eucalyptus aos 2 e 4 anos de idade e em solos com diferentes texturas; b) avaliar a razão entre o índice de área foliar (IAF) e o índice de área radicular (IAR) entre diferentes materiais genéticos de eucalipto; e c) avaliar se a relação entre a altura média do povoamento e a profundidade máxima atingida pelas raízes finas, já encontrada em uma monoprocedência de E. grandis, é válida para outros materiais genéticos. Para a coleta de raízes no solo, foi utilizado um trado semimecanizado que coletou amostras de solo a várias distâncias das árvores, até atingir 17 m de profundidade. As raízes finas (diâmetro ≤ 2 mm) e as folhas foram escaneadas e analisadas pelos softwares WinRhizo e ImageJ, respectivamente. A densidade de raízes finas entre os materiais genéticos estudados foi maior nas camadas superficiais do solo, atingindo valores de 0,2 a 0,4 g kg-1, reduzindo-se a valores menores que 0,1 g kg-1 abaixo da profundidade de 25 cm, independentemente do material genético. O material seminal e os clones exibiram um padrão similar no desenvolvimento de suas raízes finas em camadas profundas do solo. Entretanto, há uma tendência de maior densidade média de raízes finas para o material seminal e o clone 14 em comparação aos outros clones. Os perfis de conteúdo de água no solo mostraram que todos os materiais genéticos foram capazes de absorver água até 10 metros de profundidade aos dois anos ...
Variability in fine roots distribution in deep ferralsols among eucalyptus spp genetic materials
Keywords: Eucalipto - Melhoramento genético; Analise foliar; Desidratação (Hídrica); Latossolos; Dehydration